Synthesis and enzymatic processing of oligodeoxynucleotides containing tandem base damage. - Bourdat, A G (1999)
Several studies have shown that ionizing radiation generates a wide spectrum of lesions to DNA including base modifications, abasic sites, strand breaks, crosslinks and tandem base damage. One example of tandem base damage induced by @OH radical inX-irradiated DNA oligomers is N -(2-deoxy-beta-d- erythro -pentofuranosyl)-formylamine/8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodGuo). In order to investigate the biological significance of such a tandem lesion, both 8-oxo-7,8-dihydroguanine and formylamine were introduced into synthetic oligonucleotides at vicinal positions using the solid phase phosphoramidite method. For this purpose, a new convenient method of synthesis of 8-oxodGuo was developed. The purity and integrity of the modified synthetic DNA fragments were assessed using different complementary techniques including HPLC, polyacrylamide gel electrophoresis, electrospray and MALDI-TOF mass spectrometry. The piperidine test applied to the double modified base-containing oligonucleotides revealed the high alkaline lability of formylamine in DNA. In addition, various enzymatic experiments aimed at determining biochemical features of such multiply damaged sites were carried out using the synthetic substrates. The pro-cessing of the vicinal lesions by nuclease P1, snake venom phosphodiesterase, calf spleen phospho-diesterase and repair enzymes including Escherichia coli endonuclease (endo) III and Fapy-glycosylase was studied and is reported.